Bioavailability of di-peptide DL-methionyl-DL-methionine in comparison to DL-methionine in weaned and growing pigs - Santos, L. S. [UNESP] (2018)
The relative bioavailability (RBV) of a dipeptide DL-methionyl-DL-methionine (DL-Met-Met) was compared with DL-methionine (DL-Met) in growing pigs (experiment 1; N-balance study) and in weaned pigs (experiment 2; performance study). In experiment 1, 42 barrows with an initial body weight (BW) of 21.0 ± 1.37 kg were assigned to 7 dietary treatments with 6 replicate/pigs per treatment in a nitrogen (N) balance study to evaluate the RBV of DL-Met-Met to DL-Met. A basal diet (BD) was formulated to be adequate for all amino acids with the exception of Met + Cys which was 68% of the requirement [4.7 g/kg standardized ileal digestible (SID) Met + Cys; 11.5 g/kg SID Lys] for 20–25 kg pigs. Three graded levels of DL-Met (0.3, 0.6 and 0.9 g/kg) and DL-Met-Met (0.306, 0.612 and 0.919 g/kg) were supplemented to the BD to create diets 2–7. In experiment 2, a total of 189 weaned pigs (initial BW of 10.2 ± 0.98 kg) were assigned to 7 dietary treatments with 9 replicates/pens of 3 pigs per treatment. The dietary treatments consisted of a Met-deficient BD (5.3 g/kg SID Met + Cys; 13.0 g/kg SID Lys) and the same 3 graded levels of DL-Met and DL-Met-Met as in Exp. 1. In experiment 1, supplementation with DL-Met or DL-Met-Met linearly decreased (P ≤ 0.01; linear) urinary N excretion and increased (P ≤ 0.02; linear) N retained (g/day), N retention (% of intake and % of absorbed). However, there was no effect of Met sources on all N balance parameters. Based on the slope-ratio regression the RBV for DL-Met-Met compared to DL-Met was estimated 111% [95% confidence interval (CI): 63-158%] for N retained (g/d), 109% (95% CI: 57-160%) for N retention (% of intake) and 98% (95% CI: 43–154%) for N retention (% of absorbed) on an equi-molar basis. In experiment 2, the overall average daily gain (ADG) and gain:feed ratio (G:F) increased linearly (P < 0.01) by supplementation with DL-Met or DL-Met-Met. The average daily feed intake increased by supplementation with DL-Met (P = 0.02) and DL-Met-Met (P = 0.09). For ADG, the RBV for DL-Met-Met was estimated 104% (95% CI: 66-141%) on an equi-molar basis by the slope-ratio. Based on G:F, the RBV for DL-Met-Met was estimated 117% (95% CI: 61–174%) on an equi-molar basis. The results of both experiments indicate that the bioavailability DL-Met-Met is not different and at least equally bioavailable as DL-Met as a Met source for pigs.